Traumatic Injuries of the Dorso-lumbar Spine, Review of Surgical Approaches - (:unkn) unknown (SUAMTHI PUBLICATIONS, 2019)
In this review we supply information on medical methods for thoraco-lumbar spine fracture management, their efficiency and complication rates, based on previously published researches and also give background information on epidemiology and classification of thoraco-lumbar fractures. We conducted a narrative review over the literature using electronic databases as; MEDLINE, and EMBASE for studies involving data on Dorso-lumbar Spine traumatic injuries, published in September 2019. Spine fractures account for a large portion of musculoskeletal injuries worldwide. A classification of back cracks is essential in order to establish a typical language for therapy indicators and results. Clinical exam, mechanism of injury, and imaging are heavily trusted to choose regarding medical versus non-surgical management.
Keywords: Dorso-lumbar spine; Injuries; Trauma; Surgical repair; POSTERIOR LIGAMENTOUS COMPLEX; THORACOLUMBAR BURST FRACTURES; CLASSIFICATION; FIXATION; SYSTEM; PLATE